Does playing football (soccer) lead to SARS-CoV-2 transmission? - A case study of 3 matches with 18 infected football players -. (16th November 2021) - Egger, Florian; Faude, Oliver; Schreiber, Sebastian; Gärtner, Barbara C.; Meyer, Tim
ABSTRACT: The risk of viral transmission of SARS-CoV-2 associated with football (soccer) training and match play is unknown. Therefore, studies on infection-relevant contacts in football are of utmost importance. A retrospective video-based analysis was performed over 3 matches with 18 SARS-CoV-2 positive players (age: 17.6 ± 3.1 years; 2 professional, 2 semi-professional and 14 youth academy players) during the pre-season in August and September 2020 in Germany. Repeated RT-PCR tests were performed in 5 of 6 teams and pre-match RT-PCR tests in 4 of 6 teams. The last RT-PCR test ranged between 5 − 14 days post-match. The most important result was that no case of virus transmission was found as documented by RT-PCR tests (and symptom monitoring up to 14 days post-match). Physical contact between contagious and non-infected players never lasted longer than 3 seconds each and the position of players during duels was almost exclusively laterally or behind each other. In conclusion, very low risk of SARS-CoV-2 transmission during football match play has been documented. Nevertheless, due to the observational retrospective design of the study, which was based on ethical reasons, inconsistent RT-PCR testing should be regarded as limitation and larger studies are needed to confirm a low probability of virus transmission.